The Influence of Female Representation in the Board of Directors on Corporate Competitive Advantage and Firm's Innovation Performance - Sari, Made Ayu Dwira Anom; Krisnadewi, Komang Ayu (Publikasi Indonesia, 2025)
This research examines how the presence of women on corporate boards influences both competitive advantage and firms’ innovation performance. The study is motivated by the heightened intensity of domestic business competition, the persistently low proportion of female board members, the researcher’s interest in the cognitive contributions of women to innovation and competitiveness, and inconsistencies in prior empirical results. Using panel data from non-financial companies listed on the Indonesia Stock Exchange during 2017–2023, the analysis excludes financial service firms due to their unique characteristics and more stringent regulations. Applying purposive non-probability sampling, 1,504 firm-year observations were obtained. The conceptual framework is grounded in Upper Echelon Theory and Social Role Theory. Data were analyzed using STATA, incorporating path analysis and the Sobel test. The results indicate that both female board representation and innovation performance positively and significantly impact a firm’s competitive advantage. However, innovation performance does not mediate the relationship between female board representation and competitive advantage. These findings provide practical implications for Indonesian policymakers, especially in designing gender quota regulations for board composition to promote gender equality in corporate governance. Although female representation remains limited, their leadership presence has a demonstrable positive effect on competitive advantage, highlighting its potential to support stronger and more sustainable business growth while enabling strategic adaptation to increasing competitive pressures.